Pengembangan Buku Panduan Program Mentoring Keagamaan Islam dalam Pembinaan Akhlak Siswa di SMA Negeri 1 Simangambat - Frimayanti Siagian; Muhammad Darwis Dasopang; Fauziah Nasution (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2025)
The success of character education in schools depends greatly on teachers as mentors and role models. However, at SMA Negeri 1 Simangambat, issues like lack of discipline and disrespect still occur. To address this, the study developed an Islamic religious mentoring program aimed at improving students’ moral character. Using a Research and Development (R&D) method based on Plomp’s model, the research involved identifying problems, designing, implementing, and evaluating a mentorship guidebook. Results showed the product is highly valid (92.63%), practical (88.17%), and effective, with an N-Gain score of 0.48 and significant improvement (t = 1.70; p = 0.00). Thus, the guidebook is appropriate for use in fostering Islamic character education at SMA Negeri 1 Simangambat.